Correction of β-thalassemia mutant by base editor in human embryos. Issue 11 (23rd September 2017) - Liang, Puping; Ding, Chenhui; Sun, Hongwei; Xie, Xiaowei; Xu, Yanwen; Zhang, Xiya; Sun, Ying; Xiong, Yuanyan; Ma, Wenbin; Liu, Yongxiang; Wang, Yali; Fang, Jianpei; et al.
Abstract: β-Thalassemia is a global health issue, caused by mutations in the HBB gene. Among these mutations, HBB −28 (A>G) mutations is one of the three most common mutations in China and Southeast Asia patients with β-thalassemia. Correcting this mutation in human embryos may prevent the disease being passed onto future generations and cure anemia. Here we report the first study using base editor (BE) system to correct disease mutant in human embryos. Firstly, we produced a 293T cell line with an exogenous HBB −28 (A>G) mutant fragment for gRNAs and targeting efficiency evaluation. Then we collected primary skin fibroblast cells from a β-thalassemia patient with HBB −28 (A>G) homozygous mutation. Data showed that base editor could precisely correct HBB −28 (A>G) mutation in the patient's primary cells. To model homozygous mutation disease embryos, we constructed nuclear transfer embryos by fusing the lymphocyte or skin fibroblast cells with enucleated in vitro matured (IVM) oocytes. Notably, the gene correction efficiency was over 23.0% in these embryos by base editor. Although these embryos were still mosaic, the percentage of repaired blastomeres was over 20.0%. In addition, we found that base editor variants, with narrowed deamination window, could promote G-to-A conversion at HBB −28 site precisely in human embryos. Collectively, this study demonstrated the feasibility of curing genetic disease in human somatic cells and embryos by base editor system.